Implementation of Village Government Policies in Distributing Direct Cash Assistance During the Covid 19 Pandemic In Pao Village, West Malangke District, North Luwu Regency - Syahiruddin Syah (Universitas Negeri Makassar, 2022)
This research is motivated by the problem where many people complain about the consequences of being not empowered in the midst of the covid 19 outbreak and from the outbreak resulting in a decline in people's welfare, some even lose their livelihoods due to large-scale social restrictions or PSBB, therefore the government takes firm steps by empowering the community through direct cash assistance programs using a budget sourced from village funds at the implementation stage there are still many people who complain about the consequences of not receiving the assistance, so the issue arises that the village government is considered not neutral in distributing the assistance. In general, this study aims to determine the process of implementing village government policies in distributing direct cash assistance during the COVID-19 pandemic in Pao Village, West Malangke District, North Luwu Regency. This study uses qualitative research methods with a descriptive approach to data collection techniques in the field using interview, observation and documentation techniques. Based on the results of research in the field using Edward III's policy implementation theory with several indicator approaches, namely communication. , facilities, information and authority and bureaucratic structure. From the results of this study found a conclusion that the direct cash assistance program has been running as it should but has not been able to empower the community as a whole due to the very limited quota of beneficiaries.